2015
DOI: 10.1021/acs.est.5b01281
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Attachment Inhibition through Low-Voltage Electrochemical Reactions on Electrically Conducting Membranes

Abstract: Bacterial biofilm formation on membrane surfaces remains a serious challenge in water treatment systems. The impact of low voltages on microbial attachment to electrically conducting ultrafiltration membranes was investigated using a direct observation cross-flow membrane system mounted on a fluorescence microscope. Escherichia coli and microparticle deposition and detachment rates were measured as a function of the applied electrical potential to the membrane surface. Selecting bacteria and particles with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 98 publications
5
104
0
Order By: Relevance
“…The inhibition of microbial attachment was also demonstrated in experiments involving CNT/polyvinyl alcohol composite materials and E. coli [121]. The inhibition of bacterial cell attachment was achieved when the membrane was operated as either an anode or a cathode.…”
Section: Resistance To Foulingmentioning
confidence: 97%
“…The inhibition of microbial attachment was also demonstrated in experiments involving CNT/polyvinyl alcohol composite materials and E. coli [121]. The inhibition of bacterial cell attachment was achieved when the membrane was operated as either an anode or a cathode.…”
Section: Resistance To Foulingmentioning
confidence: 97%
“…As can be seen, unlike electroultrafiltration processes with electrodes on each side of the membrane, the external electric field terminates with the poly(vinyl-alcohol)carbon nanotube layer, which is upstream of the semipermeable, polymeric membrane. Jassby et al [5][6][7][9][10][11] developed methods of coating commercial polymeric UF membranes with a thin layer of a poly(vinyl-alcohol) (PVA) polymer cross-linked with multiwalled carbon nanotubes to form highly electrically conductive PVA-CNT composite membranes. In a study of the effect of moderate applied electric potentials (-1.5 and -3.4 V vs Ag/AgCl references) on fouling of high concentrations (3-5 g/L) of synthetic wastewater containing negatively charged alginic acid during EUF using PVA-CNT composite membranes, Dudchenko and Jassby et al observed substantial fouling inhibition and reduction of operating pressure in a constant flux system [6].…”
Section: Fig 1 Schematic View Of Crossflow Electroultrafiltration Wimentioning
confidence: 99%
“…Additionally, appropriate electric fields and surface charges alike were shown to affect bacteria and other microbes . If a membrane surface has a sufficiently strong electric charge or applied current, it can deactivate and repulse them . Polymer composite membranes prepared by several groups showed a good membrane performance and a very high electrical conductivity …”
Section: Introductionmentioning
confidence: 99%
“…[25,26] If a membrane surface has a sufficiently strong electric charge or applied current, it can deactivate and repulse them. [9,27] Polymer composite membranes prepared by several groups showed a good membrane performance and a very high electrical conductivity. [8,9,28,29] In a previous work, the preparation of electrically conductive, porous membranes from amorphous polyetherimide using powder particles decorated with multiwalled carbon nanotubes was shown to be an effective and simple approach to generate a MWCNT network.…”
Section: Introductionmentioning
confidence: 99%